Sustainability initiatives and the stakeholders involved : a case study of the GOLDEN Project and the electric utility industry - Murdoch-Hayes, Justin (2017)
This piece of research focuses primarily on which are the main types of sustainability initiatives within the electric utility sector with direct attention on five companies being Eletrobras, Rheinisch-Westfälisches Elektrizitätswerk AG, Fortum, Copel and Edison. Additionally this research looks at the primary stakeholders who are both the drivers and recipients of these specific set of sustainability initiatives.